Reviewing Phlomis rigida Labill From Turkey as a Antimicrobial Efficacy - Sönmez, Pınar Erecevit; Kirbağ, Sevda; Çakilcioğlu, Uğur (Sakarya University, 2020)
This work researched the inhibitory properties of the extract of Phlomis rigida Labill plant including chloroform on gram-negative and positive bacteria, yeasts and dermatophyta; the related plant is used for therapeutic purpose in public. For the disk diffusion method, this extract is effective on Pseudomonas aeruginosa that is one of the negative bacterias by 11.33 ± 0.57 mm inhibition areas. Regarding other bacterias, the effect of the related extract is so low in avoiding the improvement of Escherichia coli, Staphylococcus aureus and Bacillus megaterium by 8.33 ± 0.57 mm inhibition area. It has highly effective on Trichopyton sp. and Candida albicans that are from dermatophytes fungis and yeast by 16.33 ± 0.57 mm inhibition area. About yeast and dermatophytes fungi it has a remarkable impact on Candida glabrata (14.33 ± 0.57 mm inhibition area), Epidermophyton sp. (12.33 ± 0.57 mm inhibition area). Antimicrobial activity of this natural extract against all the microorganisms that were tested by MIC method by concentrations vary by 100 uL and 6.25 uL. Acording to this; the results showed good inhibitory effect with 6.25 ?L for C. albicans, Trichophyton sp. with 12.25 ?L for C. glabrata. In the other hand it is effective with 25 ?L for P. aeruginosa, Epidermophyton sp. with 50 ?L for E. coli, S. aureus, B. megaterium. Being used plants for medical purposes as from since the early ages show that these plants can be used as alternatives of available antibiotics; including important medical components is the other reason for being an alternative at the same time. Concerning results, P. rigida can be utilized as a therapeutic drug for the healing of infections caused by microorganisms. In this study, we believe that the P. rigida is important in the search for new antibiotics and will contribute to the literature and the world of drug as it affects different types of microorganisms at the lowest level for the first time. © 2020, Sakarya University. All rights reserved.
Keywords: bacteria; dermatophyta; Phlomis rigida Labill; therapeutic medicine; yeast